2020
DOI: 10.1007/s11092-020-09315-x
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies in purposes of student course evaluations: what does it mean to be “satisfied”?

Abstract: Student evaluation of teaching is a multipurpose tool that aims to improve and assure educational quality. Improved teaching and student learning are central to educational enhancement. However, use of evaluation data for these purposes is less robust than expected. This paper explores how students and teachers perceive how different student evaluation methods at a Norwegian university invite students to provide feedback about aspects relevant to their learning processes. We discuss whether there are character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 62 publications
0
38
0
5
Order By: Relevance
“…Medical institutes must sustain a high education standard as their graduates carry great responsibilities for which purpose evaluations are carried out to equate control with accountability and quality enhancement [16][17][18][19][20]. Institutes use systems to provide feedback to their teachers in order to improve their performance and frequent written feedback is one way to increase teacher evaluation scores, but despite an overall encouraging attitude towards evaluations, it has been observed that use of evaluation data for teaching improvement is less [8,21]. Evidence suggests that student satisfaction is closely related to tangible action taken after they provide teacher feedback [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Medical institutes must sustain a high education standard as their graduates carry great responsibilities for which purpose evaluations are carried out to equate control with accountability and quality enhancement [16][17][18][19][20]. Institutes use systems to provide feedback to their teachers in order to improve their performance and frequent written feedback is one way to increase teacher evaluation scores, but despite an overall encouraging attitude towards evaluations, it has been observed that use of evaluation data for teaching improvement is less [8,21]. Evidence suggests that student satisfaction is closely related to tangible action taken after they provide teacher feedback [22].…”
Section: Discussionmentioning
confidence: 99%
“…Little research exists on qualitative evaluation methods compared to quantitative ones [26]. But in a study published in January 2020, it was observed that open-ended questions providing space for explanation of low teachers ratings were considered important by students specially in questionnaires having non-specific questions [21]. We had modified the 2018 feedback questionnaire to target specific qualities, e.g., time management, command on subject, outlining learning outcomes, conduction of interactive sessions in a safe learning environment, use of real-life experiences, multiple teaching aids and innovative teaching methods, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during the 1970s in the USA, its use started to expand to human resources decisions concerning faculty personnel. Then, at the beginning of the new millennium, in the course of increased international cooperation and competition, a process of legalising quality for higher education institutions started, which created a need for practices of accountability (Borch et al 2020;Donzallaz 2010;Skedsmo 2020;Spooren et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To date the often simultaneous use of the method for different purposes has been critically discussed by practitioners and researchers alike, and various alternative or supplementary approaches have been tested, suggested, and implemented to address different stakeholders' need for different information (e.g. Borch et al 2020;Skedsmo 2020;Spooren et al 2017). However, as the institutional accreditation of higher education institutions will continue to be a vital requirement and, as mentioned above, this survey method produces comparable results with relative ease, higher education institutions will likely continue to rely on this method.…”
Section: Introductionmentioning
confidence: 99%